Spells to Repel Supernatural Beings in the Beliefs of the Sundanese Community - NFN Rahmawati; NFN Hendrokumoro (Balai Bahasa Kalimantan Tengah, 2023)
The rapid development of technology can erode local culture, including myths. This study aims to document spells to repel supernatural beings in the beliefs of the Sundanese community. Specifically, this study aims to describe the form, meaning, function, context of use, and relevance of spells to repel supernatural beings in the Sundanese community. This study used qualitative descriptive methods. Data were obtained from interviews and questionnaires. The informants for this study consisted of one shaman and 58 respondents. The interview was conducted on 14 and 26 September 2023. The questionnaire was distributed on 22-25 September 2023. The results of this study show that first, the form and meaning of the spell to repel supernatural beings in the beliefs of the Sundanese community are the lingual forms of anak bedul, anak kunyuk, anak monyet, mata peda, aki, and nini. Second, Sundanese people view the existence of supernatural beings not as a myth. Third, the majority of the Sundanese community thinks that the spell to repel supernatural beings functions to ask for protection from God. Fourth, the spell to repel supernatural beings is only used when visiting empty/abandoned, dirty, and damp places. Fifth, the majority of research respondents considered that supernatural creature barrier spells are still very effective to use in the present and the future. Abstrak Dewasa ini, perkembangan teknologi berpotensi menggerus budaya lokal, tidak terkecuali mitos. Penelitian ini bertujuan untuk mendokumentasikan mantra penghalang makhluk gaib dalam kepercayaan masyarakat Sunda. Secara khusus, penelitian ini bertujuan untuk mendeskripsikan bentuk, makna, fungsi, konteks penggunaan, dan relevansi mantra penghalang makhluk gaib bagi masyarakat Sunda. Agar tujuan penelitian dapat tercapai, penelitian ini menggunakan metode deskriptif kualitatif. Data penelitian diperoleh dengan teknik wawancara dan teknik sebar kuesioner. Adapun informan penelitian ini terdiri atas satu orang dukun dan 58 responden. Pengumpulan data dilaksanakan pada tanggal 14 dan 26 September 2023 (wawancara) dan tanggal 22 s.d. 25 September 2023 (sebar angket kuesioner). Penelitian ini menemukan lima temuan. Pertama, bentuk dan makna mantra penghalang makhluk gaib yang menunjukkan bahwa masyarakat Sunda memercayai makhluk gaib adalah bentuk lingual anak bedul, anak kunyuk, anak monyet, mata peda, aki dan nini. Kedua, masyarakat Sunda memandang keberadaan makhluk gaib bukanlah sebuah mitos. Ketiga, mayoritas masyarakat Sunda menganggap bahwa fungsi mantra penghalang makhluk gaib adalah untuk memohon perlindungan kepada Allah Swt.. Keempat, mantra penghalang makhluk gaib hanya digunakan pada saat mendatangi tempat kosong/terbengkalai, kotor, dan lembap. Kelima, mayoritas responden penelitian menganggap bahwa mantra penghalang makhluk gaib masih sangat ampuh digunakan pada masa kini dan masa mendatang.